A cold standby repairable system with the repairman having multiple vacations and operational, repair, and vacation times following phase-type distributions. Issue 4 (16th February 2016) - Liu, Baoliang; Cui, Lirong; Wen, Yanqing; Guo, Furi
ABSTRACT: This paper studies a cold standby repairable system with two identical components and one repairman having multiple vacations applying matrix-analytic methods. The lifetime of the component follows a phase-type distribution. The repair times and the vacation times of the repairman are governed by different phase-type distributions, respectively. For this system, the Markov process governing the system is constructed. The system is studied in a transient and stationary regime, the availability, the reliability, the rates of occurrence of the different types of failures, and the working probability of the repairman are calculated, respectively. A numerical application is performed to illustrate the calculations.